2018
DOI: 10.1142/s1088424618500505
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation behavior of unsubstituted magnesium porphyrazine in monolayers at air–water interface and in Langmuir–Schaefer films

Abstract: The aggregation behavior of unsubstituted magnesium porphyrazine (MgPz) was studied in layers at the water–air interface and in Langmuir–Schaefer films. Regions of existence and characteristics of the structure and properties of stable nanostructured monolayers of MgPz were determined with the method of quantitative analysis of compression isotherms of floating layers in a wide range of initial surface coverage degrees (ISCD). MgPz on the water surface forms monolayers of three types: a face-on type and two ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The structure of the floating layers was analyzed within the framework of an original model and method for quantitative analysis of compression isotherms of nanostructured M-monolayers. Details can be found in the Supporting Information (Note 2) and in previous works. , The structure and other characteristics of the floating layers were calculated and described in the Supporting Information (Note 3). The data were analyzed by using Origin version 7.5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the floating layers was analyzed within the framework of an original model and method for quantitative analysis of compression isotherms of nanostructured M-monolayers. Details can be found in the Supporting Information (Note 2) and in previous works. , The structure and other characteristics of the floating layers were calculated and described in the Supporting Information (Note 3). The data were analyzed by using Origin version 7.5.…”
Section: Methodsmentioning
confidence: 99%
“…Details can be found in the Supporting Information (Note 2) and in previous works. 34,36 The structure and other characteristics of the floating layers were calculated and described in the Supporting Information (Note 3). The data were analyzed by using Origin version 7.5.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, nanostructures of numerous biomolecules having different properties from those of the parent molecules and with great potential for various applications have been reported. , Self-assembly is a key player in material nanoarchitectonics, the nanostructures formed in this way arising from molecules carrying side groups that promote the process. Supramolecular polymers have been created using diverse self-assembly strategies. , The formation of different kinds of molecular assemblies from precursor compounds at the water surface has been reported. , We previously demonstrated the possibility of supramolecular design at the air–water interface by controlling the self-assembly of tetrapyrrole compounds into 2D and 3D nanostructures. The concept of nanostructuring of organic compounds at the air–water interface and a model of a floating layer, the structural units of which can be both individual molecules (Langmuir’s approach, special case) and their major nanostructures (so-called M-nanostructures, general case), were presented. The formation of the porphyrin supermolecules from magnesium porphine, a functional element of chlorophyll, was reported …”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] It was shown that porphyrins and their derivatives are capable to form stable M (Major)-nanoaggregates 5-20 nm in size at the air-water interface. [18][19][20][21] In our previous studies we demonstrated that the supramolecular design with controlled self-organization of organic compounds in 2D and 3D nanostructures at the air-water interface becomes possible if quantitative information about the structure of the floating layer is available. The quantitative method for analyzing of compression isotherms of floating layers allows determination of the critical characteristics of the layers.…”
Section: Introductionmentioning
confidence: 99%